Histopathological changes in the hepatopancreas of Lamellidens marginalis exposed to cadmium in winter - Yasmeen, Shaikh; Suryawanshi, G D; Mane, U H (International Multidisciplinary Research Journal, 2012)
In the present study, the destruction of the basement membrane of the hepatic tubules and cell surface of the digestive cells after cadmium exposure probably caused disfunction of the surface receptors resulting in the disturbance of the lysosomal system functioning.